Religious Moderation in Madrasah Curriculum: Building a Moderate Generation - Faizol, Mohammad; Syarif, Zainuddin; Kosim, Mohammad; Maimun, Maimun (Universitas Muhammadiyah Magelang, 2024)
This study examines the integration of religious moderation values ​​in the curriculum at MTs Al-Hasan, Proppo District. Observations showed that the implementation of religious moderation is less optimal, indicated by student intolerance, poor teacher understanding, and lack of activities that support moderation education. This study aims to understand how the values ​​of religious moderation are integrated into the curriculum to form moderate and inclusive mindsets in students. Using a qualitative approach, data was collected through in-depth interviews and observations involving the head of the madrasah, teachers, and students. The findings showed that religious moderation is implemented through an integrated curriculum, using themes that link subjects in Islamic Religious Education, to encourage students to embrace diversity and uphold their religious principles. This study emphasizes the importance of curriculum design in forming students' attitudes that respect differences and promote tolerance.